2002
DOI: 10.1152/ajpheart.00442.2002
|View full text |Cite
|
Sign up to set email alerts
|

No ischemic preconditioning in heterozygous connexin43-deficient mice

Abstract: Protein kinase C⑀ (PKC⑀) plays a central role in ischemic preconditioning (IP) in mice and rabbits, and activated PKC⑀ colocalizes with and phosphorylates connexin43 (Cx43) in rats and humans. Whether or not Cx43 contributes to the mechanism(s) of IP in vivo is yet unknown. Therefore, wild-type (n ϭ 8) and heterozygous Cx43-deficient mice (n ϭ 8) were subjected to 30 min occlusion and 120 min reperfusion of the left anterior descending coronary artery. IP was induced by one cycle of 5 min occlusion and 10 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(145 citation statements)
references
References 19 publications
5
136
2
2
Order By: Relevance
“…Consistent with previous results, infarct size with vehicle control was comparable in C57BL/6J mice, Cx43-deficient mice, and Cx43 WT littermates ( Fig. 4A) (17). SB216763 (70 μg/kg) significantly reduced infarct size in C57BL/6J mice [46.9 ± 4.6%, n = 7, vs. control (57.8 ± 3.5%, n = 7); P < 0.05] without altering Cx43 protein levels in plasma membrane and mitochondria (Fig.…”
Section: See Retraction Published December 10 2012supporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous results, infarct size with vehicle control was comparable in C57BL/6J mice, Cx43-deficient mice, and Cx43 WT littermates ( Fig. 4A) (17). SB216763 (70 μg/kg) significantly reduced infarct size in C57BL/6J mice [46.9 ± 4.6%, n = 7, vs. control (57.8 ± 3.5%, n = 7); P < 0.05] without altering Cx43 protein levels in plasma membrane and mitochondria (Fig.…”
Section: See Retraction Published December 10 2012supporting
confidence: 92%
“…We used the in situ mouse heart model, as described previously (9,17). Briefly, male mice, as indicated, were anesthetized with pentobarbital sodium (80 mg/kg administered i.p.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of Cx43 in mitochondria from rat, mouse, pig, and human myocardium has been demonstrated (2,15,34). The first evidence that Cx43 might play a role in ischemic preconditioning came from studies by Schwanke et al (40,41), and it has been demonstrated that ischemic preconditioning increases the amount of mitochondrial Cx43, before the prolonged ischemia (2,34). In the present study, we did not demonstrate an increased Cx43 expression in cell homogenates after sublethal ischemic stress…”
Section: Discussioncontrasting
confidence: 44%
“…In addition, substantial evidence supports the hypothesis that the protective effect may be explained, at least in part, by contribution from gap junction-mediated intercellular communication (8,14,16,19,39). Schwanke et al (40) showed that a 50% reduction in Cx43 content was sufficient to abolish the infarct-sparing effect of preconditioning strongly indicating a role for Cx43.…”
Section: Introductionmentioning
confidence: 90%